Conservation genetics of a Gondwana relict rainforest tree, Nothofagus moorei (F. Muell.) Krasser - Schultz, Lee (Queensland University of Technology, 2008)
Nothofagus moorei is a long-lived, Gondwana relict cool temperate rainforest tree. Nothofagus-dominated rainforests were widespread across much of eastern Australia during the mid-Tertiary but today, N. moorei occurs only as a series of disjunct, isolated populations in south-east Queensland and northern New South Wales. Clonal regeneration via coppicing is reported to be a common feature of most N. moorei populations, while successful sexual regeneration is believed to be rare, occurring largely only in niches with high light levels and limited competition. While clonal propagation enables population persistence and individual longevity, it cannot generate novel genotypes. Isolated populations, potentially high levels of clonality, low-potential for successful sexual regeneration, long-lived individuals and predicted global warming effects make N. moorei vulnerable to local, if not total, population extinction. The current study aimed to assess the relative conservation status of extant N. moorei populations in order to develop appropriate conservation management strategies for long-term population persistence. Levels of genetic diversity and population structure were examined across the remaining natural distribution of N. moorei using nuclear amplified fragment length polymorphism (AFLP), microsatellite and chloroplast DNA markers. In total 607 individuals were sampled from 20 populations and 5 geographical regions: Lamington/Border Ranges, Ballow, Dorrigo/New England, Werrikimbe and Barrington. Genetic results were then analysed to assess conservation status of each population and geographical region. Microsatellite and AFLP data identified comparatively high levels of genetic diversity in all remnant populations sampled. The prevalence of coppicing in the northern Lamington/Border Ranges populations appears to have had little impact on relative levels of genetic diversity, heterozygosity or population structure. Population differentiation was limited, with the majority of genetic variation retained within ...